Testing traffic density of a heterogeneous stochastic queueing system using SPRT. Issue 1 (14th January 2021) - Sagir, Murat; Saglam, Vedat
Abstract: We aim to determine the traffic density of the system as a control method in queuing systems and to keep it at the desired level. This article expands the sequential probability ratio test (SPRT) method in the heterogeneous server queuing system, which gives more accurate results in modeling a real-life case. Controlling the traffic density of the heterogeneous server queuing system can be used to determine optimal policies for the system.